2017
DOI: 10.15761/iod.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery for obese live kidney donors: an analysis of risks and benefits

Abstract: Background: Obesity can be a barrier to live donor selection and there are reports of obese live kidney donors (OLKDs) undergoing bariatric surgery prior to donation. While this practice has potential promise, the risks associated with it are unclear. Thus, our aim was to evaluate the advantages and disadvantages of this practice.Design: Risks and benefits were ascertained from the literature. Analysis of costs and benefits was performed to provide objective data for each scenario.Results: Live kidney donation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 38 In another study, bariatric surgery prior to living kidney donation by an obese donor was also found to be cost-effective (with a ratio of 3.64 vs. a kidney transplant from a deceased donor). 39 In our survey, donor candidates with resolved DM postbariatric surgery due to weight reduction could be considered for donation as soon as surgery was possible or when their BMI reduced to less than 30. However, more respondents (44%) preferred to have a waiting period postbariatric surgery to ensure no relapse.…”
Section: Discussionmentioning
confidence: 99%
“… 38 In another study, bariatric surgery prior to living kidney donation by an obese donor was also found to be cost-effective (with a ratio of 3.64 vs. a kidney transplant from a deceased donor). 39 In our survey, donor candidates with resolved DM postbariatric surgery due to weight reduction could be considered for donation as soon as surgery was possible or when their BMI reduced to less than 30. However, more respondents (44%) preferred to have a waiting period postbariatric surgery to ensure no relapse.…”
Section: Discussionmentioning
confidence: 99%